Revision workshops in elementary mathematics enhance student performance in routine laboratory calculations - Sawbridge, Jenny L.; Qureshi, Haseeb K.; Boyd, Matthew J.; Brown, Angus M. (American Physiological Society, 2014)
The ability to understand and implement calculations required for molarity and dilution computations that are routinely undertaken in the laboratory are essential skills that should be possessed by all students entering an undergraduate Life Sciences degree. However, it is increasingly recognized that the majority of these students are ill equipped to reliably carry out such calculations. There are several factors that conspire against students' understanding of this topic, with the alien concept of the mole in relation to the mass of compounds and the engineering notation required when expressing the relatively small quantities typically involved being two key examples. In this report, we highlight teaching methods delivered via revision workshops to undergraduate Life Sciences students at the University of Nottingham. Workshops were designed to 1) expose student deficiencies in basic numeracy skills and remedy these deficiencies, 2) introduce molarity and dilution calculations and illustrate their workings in a step-by-step manner, and 3) allow students to appreciate the magnitude of numbers. Preworkshop to postworkshop comparisons demonstrated a considerable improvement in students' performance, which attenuated with time. The findings of our study suggest that an ability to carry out laboratory calculations cannot be assumed in students entering Life Sciences degrees in the United Kingdom but that explicit instruction in the form of workshops improves proficiency to a level of competence that allows students to prosper in the laboratory environment.